Antioxidant Properties and Protective Effect of Phenolic Extracts of Olive Leaves and Olive Mill Wastewater against Lipid Peroxidation - Fatiha Abdellah (Innovations in Biological Science Vol. 6, 2024)
The aim of this study was to evaluate the In vitro antioxidant activity of the phenolic extracts of olive leaves and olive mill wastewater and their protective effect against lipid peroxidation. The antioxidant activity of two varieties (Chemlal and Sigoise) of the tested olive leaves and olive mill wastewater was evaluated using three different antioxidant assays (DPPH radical scavenging test, ferric reducing antioxidant power (FRAP) assay, and hydrogen peroxide scavenging assay). The protective effect of the tested extracts against lipid peroxidation in an in vitro model of rat liver homogenate was evaluated through the production of thiobarbituric acid reactive substances (TBARS). The obtained results showed that the phenolic extracts of olive leaves and olive mill wastewater are rich in phenolic compounds mainly flavonoids, with the highest content found in the extract of Chemlal olive leaves (88.35±0.73 mg GAE/g of extract for polyphenols and 45.98±0.36 mg QE/g of extract for flavonoids). Furthermore, significant anti-free radical activity and reducing power have been shown by the tested extracts. In fact, hydrogen peroxide (H2O2) can be neutralized by the studied extracts. The extract of Chemlal olive leaves exhibited the most important antioxidant activity. The tested extracts showed a significant decrease in malonic dialdehyde (MDA) levels and a protective effect against lipid peroxidation. The high protective effect was exhibited by the phenolic extract of Chemlal olive leaves. According to the obtained results, it appears that the phenolic extracts of olive leaves and olive mill wastewater have an important antioxidant potential and protective effect against lipid peroxidation and they can be used as natural antioxidant agents in food and pharmaceutical industries.